EKO-RELIGIUS: MENGGAGAS RELASI ISLAM DAN MASA DEPAN ETIKA LINGKUNGAN - Syihabuddin, Muhammad; Zulfi Mubaraq; M. Lutfi Mustofa (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2023)
Environmental problems become humanitarian problems, such as damaged area layers, erosion, and disease outbreaks that make the ecosystem unbalanced, which will endanger humans. Meanwhile, the discussion of Islamic relations and environmental ethics has always continued to be debated, ranging from handling and solving to sustainable businesses. This paper aims to elucidate the eco-religious paradigm and implications of ecological ethics in Islamic studies, including environmental movements. The study employs the analytical descriptive literature research issue. Islamic study and environmental ethics functionally serve as a tool or media that provides insight into various approaches to comprehending the relationship between Islam and environmental ethics so as not to be trapped in the fanaticism of secularism and human arrogance in dealing with nature. This study contributes theoretically through relationship theory, inter-relationship to interaction in terms of religious and environmental ethics points of view. Also, it seeks to make practical contributions in the form of human spiritual awareness to preserve the environment as a form of constructing natural values (hablu min al-‘alam). Furthermore, environmental ethics continues to evolve, adjusting to the need to assemble harmony in the future.